The Unexpected Hanging Paradox from an AI Viewpoint - Gams, Matjaž (Informatica, 2014)
This position paper hypothesizes that humans are becoming smarter, not only when using ICT and AItools, but on their own, particularly due to the progress of AI knowledge. As is common whendemonstrating that one computing mechanism is stronger than another, we chose a well-known task –the unexpected hanging paradox –that humans were previously unable to resolve efficiently, but cannow do so thanks to new knowledge. We show that the cause of prior problems was with ambiguousdefinition, as it was in the case of the liar paradox.